Toward greater insights on pharmacokinetics and exposure–response relationships for therapeutic biologics in oncology drug development. Issue 5 (15th March 2017) - Wang, Y; Booth, B; Rahman, A; Kim, G; Huang, SM; Zineh, I
Abstract : There has been increased interest in optimizing dosing regimens for oncology products over the past decade. Investigations to refine dosing regimens often occur after new drug approval.1 There is growing focus on the use of exposure–response (ER) approaches to identify optimal dosing regimens for therapeutic biologics. Herein, we describe several recent observations that have informed our thinking on the use of ER analyses in the dose regimen optimization of therapeutic biologics developed to treat cancer.